Urgensi Penyesuaian Perubahan Data Perseroan Terbatas dalam Sistem Administrasi Badan Hukum - Ni Made Elly Pradnya Suar; Putu Ayu Sriasih Wesna; Anak Agung Istri Agung (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
A Limited Liability Company as a legal entity is required to update and adjust its corporate data in accordance with the provisions of the Company Law (UUPT). These obligations include amendments to the articles of association, changes to company administrative data, and reporting Beneficial Ownership information integrated with the Legal Entity Administration System (SABH) and the Online Single Submission Risk-Based Approach (OSS-RBA) system. This study aims to examine the juridical urgency of updating corporate data and to analyze the legal consequences of non-compliance, which may result in the blocking of SABH access and disruption of business activities. This research employs a normative legal method using statutory and conceptual approaches supported by primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that updating corporate data is essential for ensuring legal certainty, transparency, and corporate accountability. Failure to fulfill these obligations, including Beneficial Ownership reporting, may lead to administrative sanctions such as written warnings, suspension of SABH access, and obstacles in taxation and business licensing processes through OSS-RBA. The blocking of SABH access restricts companies from carrying out certain legal actions and may affect business continuity. In practice, notaries play a strategic role in facilitating corporate data adjustments through the AHU Online system. Therefore, greater corporate compliance and improved synchronization of legal administration systems are necessary to support legal certainty and a transparent business environment.